Components of tax planning and characteristics of top management team - Nor Shaipah Abdul Wahab, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Tax planning activities can be detrimental to the welfare of a country’s nations. Firms’ tax planning strategies can be classified according to the activities’ components, i.e. permanent, temporary and statutory tax rates differences. Upper echelons theory explains top management team (TMT) as corporate elite whose decisions can be predicted through its members’ cognitive, value and perceptions. This study therefore attempts to examine the extent the characteristics of TMT members, in terms of age, tenure, education and gender, can explain tax planning strategies, consisting permanent, temporary and statutory tax rates differences. The sample is 216 Malaysian listed firms from 2008 to 2015. This study finds that tenure and education explain tax planning and permanent differences negatively. In contrast, tenure affects statutory tax rates differences positively. This study contributes to literature and practice by providing further evidence to support upper echelons theory in explaining the influence of TMT on tax strategies. This study also provides new evidence of tax strategies from a governance perspective. The findings suggest to the tax authority that TMT characteristics are additional factors to be considered in tax audit framework. The study also contributes to public by highlighting that TMT characteristics are useful to predict tax planning strategies.